EFFECTIVENESS UTILIZATION MS EXCEL IN NUMERICAL METHODS COURSE - firmansyah, muhammad arie; Raharjo, Sigit; Yenni, Yenni; Pradja, Barra P; Andriyani, Retno (Prima: Jurnal Pendidikan Matematika, 2025)
AbstractBuild learning innovative Can done with method utilise application Ms Excel on the eyes studying method numeric in material interpolation . Purpose study This is know effectiveness utilization Ms Excel in learning method Numerical in Mathematics Education study program faculty teaching and science education at Muhammadiyah University of Tangerang. Study This use study experiment Which compare performance Study mathematics 7th semester student of Mathematics Education study program, Muhammadiyah University of Tangerang Ms Excel And Which No utilise MS Excel. Treatment given is utilization Ms Excel in learning eye studying method numerical . Research results This shows the average difference performance Study statistics that utilize Ms Excel in learning is 68.4 while group student Which No utilise is 80.9. Results t test shows mark significance 0.001, with a significance level of 0.05 which means There is difference performance Study statistics student between those who use it and those who don't utilise Ms Excel. So can concluded that learning with Ms Excel on statistics give influence in a way significant.